Abrasion Disaster Profile, Impact And Abrasion Mitigation Efforts In East Java Province - Muhammad Ishak (Publikasi Indonesia, 2023)
Climate change causes sea waves to become stronger and affect coastlines due to abrasion. Abrasion is when local sea levels rise and drive strong waves that erode or wash away rocks, soil, and other materials. Based on data collected from the National Disaster Management Agency, there were 496 reports of disasters caused by abrasion or tidal waves. Overall, there is a trend of increasing incidents every year until it reaches a peak in 2022 with 145 reports of disaster incidents. Identifying areas prone to marine abrasion disasters based on the number of incidents in several regions, provinces, and districts is essential to carry out in order to provide appropriate mitigation measures. This research uses a systemic literature review method. This research aims to identify the general profile of abrasion disasters in East Java province. Identify the location of the incident, impact, and mitigation regarding abrasion events in East Java province. According to data from the National Disaster Management Agency, the results show that East Java Province has a high frequency of abrasion incidents, ranking first as the province with the most reports of abrasion incidents. A systemic literature review conducted on thirteen pieces of literature found that the Tuban and Situbondo areas were the most affected by abrasion incidents, with abrasion incidents occurring more frequently in the North Coast area of East Java province.